Systematic Review and Meta-analysis of Studies Evaluating Functional Rhinoplasty Outcomes with the NOSE Score. (May 2017) - Floyd, Elizabeth Mia; Ho, Sandra; Patel, Prayag; Rosenfeld, Richard M.; Gordin, Eli
Objective: To provide aggregate data regarding the ability of functional rhinoplasty to improve nasal obstruction as measured by the Nasal Obstruction Symptom Evaluation (NOSE) score. Data Sources: PubMed, EMBASE, Cochrane databases. Review Methods: A search was performed with the terms "nasal obstruction" and "rhinoplasty." Studies were included if they evaluated the effect of functional rhinoplasty on nasal obstruction with the NOSE score. Case reports, narratives, and articles that did not use the NOSE score were excluded. Functional rhinoplasty was defined as surgery on the nasal valve. This search resulted in 665 articles. After dual-investigator independent screening, 16 articles remained. Study results were pooled with a random effects model of meta-analysis. Change in NOSE score after surgery was assessed via the mean difference between baseline and postoperative results and the standardized mean difference. Heterogeneity was assessed and reported through the I 2 statistic. Results: Patients in the included studies had moderate to severe nasal obstructive symptoms at baseline. The NOSE scores were substantially improved at 3-6, 6-12, and ≥12 months, with absolute reductions of 50 points (95% CI, 45-54), 43 points (95% CI, 36-51), and 49 points (95% CI, 39-58), respectively. All of these analyses showed high heterogeneity. Conclusions: Nasal obstruction as measured by the NOSE survey is reduced by 43 to 50 points (out of 100 points) for 12 months after rhinoplasty. Our confidence in these results is limited by heterogeneity among studies, large variability in outcomes beyond 12 months, and the inherent potential for bias in observational studies.